2023
DOI: 10.3390/ijms242216468
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and Metabolic Signaling Interfaces of the Hypertrophic and Senescent Chondrocyte Phenotypes Associated with Osteoarthritis

Emőke Horváth,
Árpád Sólyom,
János Székely
et al.

Abstract: Osteoarthritis (OA) is a complex disease of whole joints with progressive cartilage matrix degradation and chondrocyte transformation. The inflammatory features of OA are reflected in increased synovial levels of IL-1β, IL-6 and VEGF, higher levels of TLR-4 binding plasma proteins and increased expression of IL-15, IL-18, IL-10 and Cox2, in cartilage. Chondrocytes in OA undergo hypertrophic and senescent transition; in these states, the expression of Sox-9, Acan and Col2a1 is suppressed, whereas the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 145 publications
(201 reference statements)
0
4
0
Order By: Relevance
“…Whether the development of OA, particularly in the knee, in the post-menopausal state is a unique subset of OA patients is unknown, but the possibility has been raised [10]. However, it is clear that OA is an inflammatory disease (discussed in [51][52][53][54]) and in early post-traumatic knee injuries leading to OA in preclinical models, treatment to inhibit inflammation ameliorates the development of the condition [55][56][57]. Furthermore, metabolic osteoarthritis has an inflammatory component [58][59][60] and this may relate to post-menopausal women with obesity.…”
Section: Variables and Factors Influencing Post-menopause Diseases An...mentioning
confidence: 99%
“…Whether the development of OA, particularly in the knee, in the post-menopausal state is a unique subset of OA patients is unknown, but the possibility has been raised [10]. However, it is clear that OA is an inflammatory disease (discussed in [51][52][53][54]) and in early post-traumatic knee injuries leading to OA in preclinical models, treatment to inhibit inflammation ameliorates the development of the condition [55][56][57]. Furthermore, metabolic osteoarthritis has an inflammatory component [58][59][60] and this may relate to post-menopausal women with obesity.…”
Section: Variables and Factors Influencing Post-menopause Diseases An...mentioning
confidence: 99%
“…Chondrocytes in OA undergo hypertrophic and senescent phenotypic transition when exposed to abnormal biomechanical and biochemical joint environment from matrix degradation products and pro-inflammatory mediators. [132][133][134][135] Although chondrocyte hypertrophy is a necessary developmental stage in endochondral ossification, the aberrant hypertrophy-like phenotype in OA chondrocytes results in irreversible cartilage destruction and initiation of OA. 132 It was reported that YAP significantly suppresses the expression of Runx2 and chondrocyte hypertrophy.…”
Section: Yap/taz and Oamentioning
confidence: 99%
“…[138][139][140] Guarnieri et al demonstrated that YAP/TAZ activity in stromal cells prevents emergence of senescent cells and SASP by restraining cGAS-STING signaling, 141 probably through the protection of nuclear envelope integrity. 135,141 In addition, mechanical cues, such as ECM stiffness and cell geometry, also induced cell senescence via YAP inhibition. 142 Moreover, YAP overexpression rejuvenates aged MSCs and inhibits cell senescence by up-regulation of forkhead box D1 (FOXD1) in a TEADdependent manner, whereas YAP knockdown results in premature senescence of MSCs due to FOXD1 inactivation.…”
Section: Yap/taz and Oamentioning
confidence: 99%
“…The chronic inflammatory microenvironment resulting from AC damage is inundated with various activated inflammatory cells and pro-inflammatory mediators, along with reactive oxygen species (ROS) [ 20 , 21 ]. During cartilage injury, overexpressed ROS not only attacks the extracellular matrix (ECM) of the AC directly but also induces lipid peroxidation and DNA cleavage, which destabilizes the microenvironment [ 22 ].…”
Section: Introductionmentioning
confidence: 99%